The performance of growing goats fed urea treated rice straw supplemented with Incum (Klienhovia hospita) foliage - Jusoh, S; Amalina M. Y. (Malaysian Journal of Animal Science, 2017)
The usage of locally available forages such as agricultural by-products and native trees is the crucial thing for goat farmers to obtain good quality feed and to reduce cost of feeding. A study was conducted to investigate the performance of crossbred goats fed urea treated rice straw supplemented with different levels of Klienhovia hospita foliage, in particular to determine the nutrient feeding value of experimental feed diets, evaluate the growth performance, feed intake and digestibility of the diets by goats. The feeding trial conducted was divided into two sections: digestibility and animal performance. The digestibility test was performed using total faecal collection method. The treatment diets were based on urea treated rice straw (RS) supplemented with commercial concentrate (C) and Klienhovia hospita (KH) herbage: T1 with 85% RS and 15% C, T2 with 85% RS and 5% KH and 10% C, T3 with 85% RS, 10% KH and 5% C, and T4 with 85% RS and 15% KH. The feeding trial used 12 6-mo old crossbred male goats divided into 4 groups with the diets offered ad libitum and had access to clean drinking water. The left over feed was removed and weighed daily to determine voluntary DM intake. The initial average body weight of goats used ranged between 20.141.03 kg and 20.290.18 kg. The animals were placed in individual metabolic crates on slatted floor of 0.8 m above ground for 100 consecutive d. The results showed that there was no significant difference observed on body weight of goats among the treatments. ADG of goats was significantly higher in goats on diets T3 and T4 than those on control diet. Significant higher feed intake was observed in goats fed diet containing KH foliage than those fed with diet T1. Results for ASH, CP and ADF digestibility among different treatments were not significantly different whereas NDF digestibility was significantly higher in T2 treatment in comparison with T1, T3 and T4. The dry matter digestibility values of T1 and T2 diets were significantly higher than that of diet T4. Thus the study indicated that feeding goats with urea treated rice straw supplemented with KH foliage gave a positive effect on growing goats replacing concentrate fed with rice straw basal diet. It is concluded that the inclusion of KH foliage in the diet of goats has improved their growth performance and feed intake.